Clerodendrum serratum: A clinical approach - Mukesh Kr. Singh, Gaurav Khare, Shiv Kr. Iyer, Gotmi Sharwan, D. K. Tripathi (Journal of Applied Pharmaceutical Science)
Clerodendrum serratum Linn. (Family: Verbenaceae) is very widely distributed in tropical and subtropical regions of the world. Ethno-medicinal importance of the plant has been reported in various indigenous systems of medicines like Ayurveda, Siddha and Unani for the treatment of various life-threatening diseases such as syphilis, typhoid, cancer, jaundice and hypertension. Some of the chief constituents found in the plant are D-mannitol, hispidulin, cleroflavone, apigenin, scutellarein, serratagenic acid, acteoside, verbascoside, oleanolic acid, clerodermic acid, γ-sitosterol, β-sitosterol, cholestanol, clerosterol, campesterol and 24-ethyl cholesterol. Traditionally, it has been also used as anti-rheumatic, anti-asthmatic, febrifuge, in cephalagia and ophthalmia. The roots of C. serratum are also used as anti-oxidant, anti-bacterial, and anti-fungal. Besides these the antimicrobial value of this herbal plant have also been reported in its stems and leaves. These reports are very encouraging and indicate that herb should be studied more expensively for its therapeutic benefits.
Keywords: Clerodendrum serratum, anti-oxidant, anti-bacterial, anti-hypertensive, anti-cancer, anti-syphilis.